Prevalence and factors associated with thoracic alterations in infants born prematurely - Davidson, Josy [UNIFESP] (2012)
OBJECTIVE: To determine the prevalence of thoracic musculoskeletal alterations and associated factors in infants born prematurely. METHODS: This was a cross sectional study with infants in the first year of age, born prematurely with birth weight < 2,000 g, who were followed up at the Premature Clinic from February, 2007 to December, 2008. Exclusion criteria were: maj or congenital malformations as defined by the Centers for Disease Control and Prevention (CDC), grade III/IV intraventricular hemorrhage, or periventricular leucomalacia. Physical examinations performed independently by two physiotherapists were used to assess shoulder elevation and thoracic retractions. Comparisons between groups were performed using the chi-squared test or Fisher's exact test for categorical variables, and Mann-Whitney's test or Student's t-test were used for continuous variables. Interobserver reliability between the two physiotherapists was assessed by the kappa coefficient. Variables associated with these thoracic musculoskeletal alterations were studied by univariate and multiple logistic analyses. Statistical differences were considered significant when p < 0.05. This study was approved by the ethical committee of the institution, and parents/guardians signed an informed consent. RESULTS: 121 infants with a gestational age of 31.1 ± 2.8 weeks and birth weight of 1,400 ± 338 g were included. Thoracic alterations were detected by Physiotherapist 1 in 81 (66.9%) infants, and in 83 (68.6%) by Physiotherapist 2 (kappa coefficient = 0.77). By multivariate logistic regression analysis, factors associated with thoracic musculoskeletal alterations were: respiratory distress syndrome (odds ratio [OR] = 3.246, 95% confidence interval [CI]: 1.237-8.732), bronchopulmonary dysplasia (OR = 11.138, 95% CI: 1.339-92.621), and low length/age ratio (OR = 4.571, 95% CI: 1.371-15.242). CONCLUSION: The prevalence of thoracic alterations was high in infants born prematurely, and was associated with pulmonary disease and low length/age ratio.